COMMUNITY PARTICIPATION IN THE PREPARATION OF THEREGIONAL GOVERNMENT WORK PLAN (RKPD)IN NYUATAN DISTRICT, WEST KUTAI REGENCY (ARNSTEIN’S LADDER OF CITIZEN PARTICIPATION MODEL) - Nila Mujuwita; Bonaventura Ngarawula; Wahyu Wiyani (International Journal of Business, Law and Political Science, 2026)
Objective:  This study aimed to analyze the level of community participation in the preparation of the Regional Government Work Plan in Nyuatan District, West Kutai Regency, based on Arnstein’s Ladder of Citizen Participation, as well as to identify the supporting and inhibiting factors affecting such participation. The study employed a descriptive approach by integrating qualitative and quantitative data. Method: Data were collected through interviews, observations, documentation, and a recapitulation of respondents’ responses. The data were analyzed using the Miles and Huberman model, which consisted of data reduction, data display, and conclusion drawing and verification.  Results: The results indicated that community participation was not situated at the level of non-participation. This was demonstrated by the predominance of strongly disagree responses for the manipulation indicator at 94.44% and the therapy indicator at 92.59%. For the informing indicator, 94.44% of respondents strongly disagreed that information was limited and communicated only in a one-way manner, although the interviews revealed that access to planning documents still needed to be expanded. The consultation and placation indicators each received 98.15% strongly agree responses, indicating that the community had been provided with opportunities to submit proposals and participate through community representatives. The partnership indicator received 92.59% strongly agree responses, delegated power received 96.23%, and citizen control received 92.59%, reflecting the development of dialogue, partnership, priority setting, and community involvement in monitoring and managing local development programs.  Novelty: Nevertheless, final decisions remained subject to governmental authority, regional priorities, and budgetary capacity. Supporting factors included the Development Planning Forum, government openness, village government support, the involvement of community leaders, and a deliberative culture. Inhibiting factors included limited public understanding, unequal access to information, inadequate feedback on proposals, geographical constraints, communication limitations, and the passivity of some community members. It was concluded that community participation tended to be positioned at the partnership level and was progressing toward delegated power, although it had not yet substantively achieved full citizen control.